Higher education and adult motivation: The case of UiTM Pahang's E-PJJ Students / Mohd Samsuri Ghazali …[et al.] - Ghazali, Mohd Samsuri; Azrol Azuan, Mohd Faizal; Syed Hamid, Sharifah Shatrah; Ab Rashid, Mohd Elfee (2013)
Although the traditional-aged college student may still be the most visible on campus, adult students are becoming the new majority in the student body. The adult student may fulfill many different roles and is now taking on the additional role of a student. Many of these adults also have the responsibility of children and jobs. The purpose of this study was to explore the motivating factors that lead Pahang workers to pursue higher education. This research was conducted using 60 students of E-PJJ Pahang Campus and the data were collected using a survey instrument that measures the extent to which various factors influenced one's motivation to pursue higher education. Analysis of the data revealed that overall the most important factor rated was "to career enhancement".